Steroid Receptor Coactivators and Their Expression, Regulation and Functional Role in Endocrine Responsive and Resistant Breast Cancer - Moi, Line L. Haugan; Flågeng, Marianne Hauglid; Fenne, Ingvild S.; Gjerde, Jennifer; Lien, Ernst A.; Mellgren, Gunnar (IntechOpen, 2011)
None